2020
DOI: 10.1016/j.csbj.2020.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vector-host-pathogen relationships using data mining and machine learning

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…We postulate that the strain-level shift in K. pneumoniae contributed to these marked alterations in ARGs and VFGs as a result of lactitol treatment. Intestinal VFGs were suggested to influence host immune homeostasis ( 41 ) and be associated with disease severity ( 42 ). Of note, we found that alterations in the composition of lactitol-treated VFGs were correlated with the strain-level changes in K.pneumonia , which accounted for shifts in the highest proportion of differentiated VFGs in the gut microbiome of patients in LC-pre vs. LC-post groups.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the strain-level shift in K. pneumoniae contributed to these marked alterations in ARGs and VFGs as a result of lactitol treatment. Intestinal VFGs were suggested to influence host immune homeostasis ( 41 ) and be associated with disease severity ( 42 ). Of note, we found that alterations in the composition of lactitol-treated VFGs were correlated with the strain-level changes in K.pneumonia , which accounted for shifts in the highest proportion of differentiated VFGs in the gut microbiome of patients in LC-pre vs. LC-post groups.…”
Section: Discussionmentioning
confidence: 99%
“…The first significant approach is supervised machine learning aiming to build up a predictive algorithm based on data analysis like regression and classification methods. Classification methods used in the prediction of infectious diseases in the past are “mixed linear regression (MLR)”, “artificial neural network (ANN)”, “decision tree (DT)”, “support vector machine (SVM)”, “Random forest (RF)”, “gradient boosting decision tree (GBDT)”, and “Bayesian Network (BN)” (e.g., Agany et al, 2020 ). The other AI approach is based on unsupervised machine learning, which permits computers to discover large amounts of unclassified data and learn treatment patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The research of machine learning combined with big data has played a more and more important role in the development and competition of various fields [19][20][21]. Applying machine learning to infectious disease early warning system can break through the limitations of traditional prediction system and achieve the purpose of real-time and dynamic early warning, thereby improving the effect of prevention and control [22,23]. Therefore, machine learning is used for global COVID-19 epidemic trend prediction, which is a direction that can be studied and applied.…”
Section: Related Work 21 Covid-19 Data Set Source and Analysismentioning
confidence: 99%